2011
DOI: 10.3109/19396368.2011.644385
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of aquaporin 7 in human sperm and its relationship with semen parameters

Abstract: Aquaporins (AQPs) are a family of 13 small hydrophobic transmembrane proteins expressed in numerous tissues and cells. Some AQPs work as strict water channels, others are permeable to a range of substances, including glycerol. In the male reproductive system their localization in testis, efferent ducts, epididymis, and spermatozoa has been described. We studied the distribution of AQP7 in ejaculated human sperm and the relationship between AQP7 labeling and sperm characteristics. Semen samples from 33 men were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 23 publications
0
30
1
Order By: Relevance
“…Nevertheless, in this study we found that during seawater activation, seabream Aqp8b is relocated from the plasma membrane of the anterior flagellum into the mitochondrion of spermatozoa, which did not occur for the other aquaporins. Although such a mechanism for AQP8 has not been previously observed in mammalian sperm, the accumulation of AQP7 in the mitochondria of human activated spermatozoa [26], as well as the presence of AQP8 in the inner membrane of the mitochondria of several tissues [84][85][86][87], has been reported. Since AQP7 and -8 are permeable to ammonia in addition to water and solutes [48,88], and AQP8 does not appear to contribute greatly to the facilitated transport of water across the mitochondrial membrane [82,89,90], it is plausible that the major function of mitochondrial AQP8 is ammonia diffusional transport [90].…”
Section: Aquaporins In Teleost Testis and Spermmentioning
confidence: 95%
See 2 more Smart Citations
“…Nevertheless, in this study we found that during seawater activation, seabream Aqp8b is relocated from the plasma membrane of the anterior flagellum into the mitochondrion of spermatozoa, which did not occur for the other aquaporins. Although such a mechanism for AQP8 has not been previously observed in mammalian sperm, the accumulation of AQP7 in the mitochondria of human activated spermatozoa [26], as well as the presence of AQP8 in the inner membrane of the mitochondria of several tissues [84][85][86][87], has been reported. Since AQP7 and -8 are permeable to ammonia in addition to water and solutes [48,88], and AQP8 does not appear to contribute greatly to the facilitated transport of water across the mitochondrial membrane [82,89,90], it is plausible that the major function of mitochondrial AQP8 is ammonia diffusional transport [90].…”
Section: Aquaporins In Teleost Testis and Spermmentioning
confidence: 95%
“…In addition, the Western blot analyses indicated that in nonactivated spermatozoa the amount of Aqp1ab and -10b in the plasma membrane seems to be lower than that of Aqp1aa, -7, or -8b. The spermatozoa of mammals also express the AQP7 and -8 orthologs, but their localization differs from that in the seabream, since AQP7 is localized in the cytoplasmic droplet and/or the middle piece of the tail and AQP8 is present as a punctuated pattern in the cytoplasmic droplet and along the tail [21,24,26,77]. The expression of Aqp10b in the head and flagella of seabream spermatozoa agrees with our previous report [7], but this is not the case for Aqp1aa, which was previously detected in the head and tail.…”
Section: Aquaporins In Teleost Testis and Spermmentioning
confidence: 98%
See 1 more Smart Citation
“…Aquaglyceroporins have been described in fat tissue, suggesting involvement in glycerol export during lipolysis, an important and novel function for these polypeptides . As well, AQP-7 has been found in human spermatozoa (Moretti et al 2011) and in the seminiferous epithelium, suggested as associated with volume regulation in germ cells ). AQP-7 has been immunocytochemically (ICC) detected in boar spermatozoa using different commercial antibodies (Prieto-Mart ınez et al 2014;Vicente-Carrillo 2015) and its role related to sperm quality (Prieto-Mart ınez et al 2014) and/or capacity to react under different osmotic pressures (Vicente-Carrillo 2015).…”
Section: Introductionmentioning
confidence: 92%
“…Aquaglyceroporins have been described in fat tissue, suggesting involvement in glycerol export during lipolysis, an important and novel function for these polypeptides 14 . As well, AQP-7 has been found in human spermatozoa 15 and in the seminiferous epithelium, being suggested as associated with volume regulation in germ cells 16 . Presumably, this AQP-7 would also provide a port for glycerol as a carbon source for mature sperm metabolism.…”
Section: Introductionmentioning
confidence: 99%